Em nome do negro, da terra e do Espírito Santo: aspectos históricos, jurídicos e políticos do reconhecimento das áreas remanescentes de quilombos no Sapê do Norte-ES - Garcia, Flávio Barroca e (2007)
This thesis brings an approach to historical, juridical and political issues which involve the recognition of the land occupied by quilombos (rebel slaves) in Brazil. Its main objectve of analyses is the relation between Law and rule established by Decree 4.887/2003 which organizes Article 68 of the Act of transitory Constitutional of the Federal Constitution of 1988. As a backgrownd issue it develops under a social-historical perspective, a discussion conceptual-historical of the formation of the quilombos communities and their achievements in trying to build a structure capable of resisting slavery. On primary and secondary sources, the investigation limits itself to historical facts that influenced in the formation of the brazilian quilombos , more precisely in Sapê do Norte , located at the extremity north of Espirito Santo. Through field research it studies the political, social and juridical impact of Decree 4.887/2003 which influenced in new approach to the signification given to the concept of remaining quilombos communities.